Kebutuhan Kapal Pengangkut Gas Alam Cair (LNG) dalam Proyeksi Perdagangan LNG Antarnegara - Muzhoffar, Dimas Angga Fakhri; Riadi, Achmad (Politeknik Bumi Akpelni, 2024)
The impact of global economic growth is reflected in commodity price fluctuations and the intensive transportation needs, particularly for LNG. The Sustainable Development Goals focus on carbon emissions until 2050 drives an increase in the demand for LNG as a clean energy source. In the context of international trade, LNG carriers through maritime routes serve as the primary means for export and import, fulfilling the need for efficient transportation. Additionally, the construction process of LNG vessels takes a considerable amount of time, with ships being ordered based on global LNG transactions. Therefore, precise estimates are crucial to support economic benefits. Through the projection of LNG trade volumes, this research aims to provide insights into the potential demand for LNG carriers. Predictions using linear regression analysis for each route indicate the potential for capacity increases up to 134% by 2042. Such conditions are in line with the projected LNG supply, expected to continuously rise until 2040 to meet the demand in both industrial and electricity sectors. These results are projected for each type of LNG carrier, where Conventional vessels are anticipated to increase significantly by up to 599 new ships. Specifically, this study offers an in-depth perspective on the dynamics of global LNG trade and potential projections of future ship requirements, opening opportunities for facility development and business process modifications in the context of LNG transportation.